First‐principles investigation of the GaN growth process in carbon‐added Na‐flux method. Issue 5 (19th November 2014) - Kawamura, Takahiro; Imabayashi, Hiroki; Maruyama, Mihoko; Imade, Mamoru; Yoshimura, Masashi; Mori, Yusuke; Morikawa, Yoshitada
Abstract We hypothesized that a nitrogen transportation process mediated by cyanide (CN) ions causes the observed increase in growth rate by carbon addition in the Na‐flux growth of GaN. Using first‐principles calculations, we investigated the probability of the nitrogen transportation process from the viewpoint of change of free energy. In addition, to verify whether the CN can separate into N and C atoms, we estimated the C–N bond energy on the GaN crystal surface by the blue‐moon method using constrained molecular dynamics simulations.